2015
DOI: 10.1155/2015/982350
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Life Analysis of Rolling Bearings Based on Quasistatic Modeling

Abstract: Rolling bearings are widely used in aeroengine, machine tool spindles, locomotive wheelset, and so forth. Rolling bearings are usually the weakest components that influence the remaining life of the whole machine. In this paper, a fatigue life prediction method is proposed based on quasistatic modeling of rolling bearings. With consideration of radial centrifugal expansion and thermal deformations on the geometric displacement in the bearings, the Jones’ bearing model is updated, which can predict the contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The parameters in this mathematical model of bearing are in ADOSE of P.K. Gupta bearing dynamics program [10] was tabulated in Table 2. The 10 spindle oil was chosen with the lubrication oil dynamic viscosity of 0 =0.027 Pa•s and viscosity coefficient =2.3e-8Pa −1 [11].…”
Section: Results Of Dynamic Characteristics the Changes Of mentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters in this mathematical model of bearing are in ADOSE of P.K. Gupta bearing dynamics program [10] was tabulated in Table 2. The 10 spindle oil was chosen with the lubrication oil dynamic viscosity of 0 =0.027 Pa•s and viscosity coefficient =2.3e-8Pa −1 [11].…”
Section: Results Of Dynamic Characteristics the Changes Of mentioning
confidence: 99%
“…A coupled spindle bearing model was established considering the centrifugal deformation by Hong et al [9], and the simulation and experimental results indicated that there is a correlation between the natural frequency and the number of bearings. The Jones' bearing model was updated by Guo et al [10], by considering of radial centrifugal expansion and thermal deformations on the geometric displacement in the bearings, which can predict the contact angle, deformation, and load between rolling elements and bearing raceways more accurately.…”
Section: Introductionmentioning
confidence: 99%
“…The contact stress in the contact zone is distributed as an ellipsoid, as shown in Figure 5. When the contact load is Q, the contact stress at any point (x, y) in the contact zone can be expressed as follows [36]:…”
Section: Figure 3 Force Distribution Of Rolling Bearings Under the Ramentioning
confidence: 99%
“…Due the importance of this matter, many papers seek to understand the mechanism of this problem. However, the study of contact between bearing parts is known to be a complex issue, since the contact area is subjected to stresses as high as 2∼5 GPa (Norton, 2013;Rycerz, Olver, and Kadiric, 2017;Morales-Espejel and Gabelli, 2015;Bhattacharyya, Londhe, Arakere, and Subhash, 2017;Li, Hu, Meng, Zhan, andShen, 2017 Arakere, 2016), as well as several other parameters that have an impact on the situation, such as lubrication, vibration, roughness (Yusof and Ripin, 2014), bearing dimensions (Chen and Wen, 2015), rotation speed, applied loads (Guo, Cao, He, and Yang, 2015), and the curvature of the inner and outer rings (Deng, Hua, Han, and Huang, 2013;Chen and Wen, 2015). Therefore, each parameter must be examined thoroughly, seeking to determine the influence of its behavior on RCF.…”
Section: Introductionmentioning
confidence: 99%